The caterpillar that roared - Lawrence, Michael; Bartlett, Alison (New York Dorling Kindersley Pub, 2000)
Hugo the caterpillar tries to convince his friends that he is a lion, until the day he frightens Maurice the minnow away and realizes that it is better to be himself
3
Keywords: Animals -- Fiction; Caterpillars -- Fiction; Self-acceptance -- Fiction